Defining the optimal revascularization strategy during protected high-risk procedures with Impella. (8th December 2022) - Sinning, Jan-Malte; Al-Rashid, Fadi; Ibrahim, Karim; Aurigemma, Cristina; Chieffo, Alaide
Abstract: Complete revascularization (CR) in patients with multi-vessel disease improves outcomes. The use of percutaneous left-ventricular assist devices, such as the Impella heart pump, is useful to minimize the risk of haemodynamic compromise in complex higher risk and clinically indicated patients. The recently published data from the PROTECT III trial suggest more CR during Impella-protected percutaneous coronary intervention with more extensive lesion preparation and treatment, resulting in the reduced need for repeat revascularization. To achieve CR and improve survival, procedural guidance by intravascular imaging, extensive lesion preparation, debulking with atherectomy devices, advanced chronic total occlusion revascularization techniques, and post-interventional treatment with modern anti-platelet medication are essential.